Diseño de un Sistema de Control de Agua de Imbibición Automatizado en Procesos de Molienda (Revista Cientifica Ingenio Magno, 2023)
The present research work was carried out in a sugar factory in the department of Lambayeque, whose imbibition water control process was performed manually by an operator, through a flow meter, causing that the imbibition water flow and the sugar cane mass were not constant, affecting the production cycle. The objective was to design an automation system for the control of the imbibition water flow in the sugar cane milling process. A mass flow meter with load cells was installed to measure the mass flow of sugar cane, and pulse encoder sensors were installed to find the times of passage of the mass flow through the mills. As a result of the automation of the process, a constant mass flow rate was established and the variables were displayed on the HMI screen with optimum resolution. The programming was developed with Vijeo Designer v6.1 software, which is a state-of-the-art application with which the user can create operator panels and configure operating parameters for user-machine interface devices. A program for the automatic imbibition water control system was developed in Twido Suite v3.2 software because of its natural relationship with the logic based on control circuits.
Keywords: Imbibition water, mass flow, grinding, load cells, encoder sensors, Vijeo Designer software, Twido Suite software.